The effect of dietary zinc on the microbiome and resistome of the gestating sow and neonatal piglets - Mary Jane Drake; Meghann Pierdon; George DeMers; Scott G. Daniel; Kyle Bittinger; Laurel E. Redding (Animal Microbiome)
Abstract Zinc is an important trace element for animal health and physiology, and it is routinely provided as a supplement in livestock diets. High levels of dietary zinc have been found to be beneficial for weanling pigs in preventing diarrhea and improving growth. It has also been associated with better reproductive performance in gestating sows and survival of neonatal piglets. However, little is known about zinc’s effect on the microbiome of the gestating sow and her neonatal piglets. Even less is known about its effects on the sow and piglet resistome, which is important because dietary zinc can co-select for antimicrobial resistance. The goal of this randomized controlled dietary feeding trial was to assess the effect of high levels of dietary zinc in the last week of gestation on the microbiomes and resistomes of the gestating sow and her neonatal piglets. Seventy-three gestating sows were randomized to receive a diet with standard zinc levels (125 ppm) or high zinc levels (2500 ppm) approximately one week prior to their anticipated farrowing date. Fecal samples were collected from sows at enrollment and at farrowing and from piglets within 3 days of parturition. Fecal samples underwent 16sS rRNA gene sequencing, and a subset of samples underwent shotgun metagenomic sequencing. Statistically significant differences in richness, diversity and taxonomic composition were observed over time, and sows in the treatment group had significantly higher alpha diversity at farrowing (p = 0.04) and significantly altered levels of 3 taxa (Turicibacter, unclassified Clostridiaceae, and unclassified Christensenellaceae). Several antimicrobial resistance genes were significantly more abundant in the zinc group at farrowing compared to the control group, including tetracycline resistance genes [tet(O); tet(W); tet(32); tet(O/W)]; aminoglycoside resistance genes (APH(3’)-IIIa), macrolide-lincosamide-streptogramin (MLS) resistance genes (lsaB; macB); and others (kdpE, Pseudomonas aeruginosa CpxR). No significant differences were observed in the piglet microbiomes or resistomes across sow treatment groups. Overall, high levels of dietary zinc had modest effects on the sow microbiome during the feeding trial. Increases in antimicrobial resistance genes in zinc supplemented sows suggest that supranutritional levels of dietary zinc should be avoided in gestating sows.